Bee Buzz.......: Review of Lisa Jean Moore & Mary Kosut, Buzz: Urban Beekeeping and the Power of the Bee - Snæbjörnsdóttir, Bryndís (Humanimalia, 2015)
Lisa Jean Moore and Mary Kosut, Buzz: Urban Beekeeping and the Power of the Bee. New York: New York University Press, 2013. 241 pp. $85.00 hb; $26.00 pb.